Dyselectrolytemia in hyperglycaemic crisis patients with uncontrolled non-insulin dependent diabetes mellitus - Rana, Anup K; Ray, Subhashree (International Journal of Research in Medical Sciences, 2017)
Background: Diabetes is a group of disorders characterized by high blood glucose levels. Disturbances in serum electrolytes sodium (Na+), potassium (K+) and chloride (Cl‑) is found in diabetes. The objective of the study was to investigate the disturbances in concentrations of serum electrolytes in hyperglycaemic crisis, uncontrolled non – insulin dependent diabetes mellitus patients: early detection and treatment of such abnormalities, leading to better quality of life of patients. Methods: Data was collected prospectively over a period of 1 year and analyzed retrospectively. Of the 131 subjects included in the study, two groups were formed; 60 hyperglycaemic diabetes mellitus patients and 71 healthy volunteer as controls. Biochemical analysis for Na+, K+, Cl- was performed by ISE method using Easy – lyte automatic electrolyte analyzer. The random glucose levels were estimated by direct Hexokinase enzymatic method using Cobas Interga 400. Unpaired t-test was done to find out the difference between the two paired groups and Pearson's correlation was calculated to know the correlations between electrolytes and random glucose levels. Results: In uncontrolled diabetes mellitus, increase in serum Na+ and Cl- levels were observed to be highly significant (p<0.001, respectively) while that of K+ showed significant (p<0.05) alterations Conclusions: The study demonstrated significant association of Na+, K+ and Cl- with hyperglycaemia in patients with hyperglycaemic crisis in uncontrolled type 2 diabetes mellitus. So, electrolytes should be measured during the treatment of type 2 diabetes mellitus.